Pendampingan Guru Pembelajar pada MGMP Melalui Metode Tutor Sebaya Dengan Pendekatan Andragogi - Artiana, Artiana (ANTHOR: Education and Learning Journal, 2022)
The purpose of writing this article is to (1) optimize the competence of student teachers through the peer tutoring method with an andragogical approach at the Chemistry MGMP "Jiang Jang Isotope" in East Barito Regency; (2) change the mindset of the Chemistry teacher at the Chemistry MGMP "Jiang Jang Isotope" East Barito Regency, Regency East Barito becomes a teacher as an agent of reform who is ready to face the Teacher Competency Test. The method of fostering and empowering the MGMP Chemistry "Isotope Jari Jenang" using the peer-to-peer method with the andragogical approach. The results obtained by implementing the Guidance and Empowerment of student teachers through the peer tutoring method with the andragogic approach can optimize the competence of teachers at the MGMP Chemistry "Isotope Jari Jang" Barito Regency Timur and was able to change his mindset as a teacher who became an agent of reform in facilitating student-centered learning and was ready to face the Teacher Competency Test (UKG).